A single lycaenid caterpillar gets an ant‐constructed shelter and uninterrupted ant attendance. Issue 12 (6th December 2019) - Ekka, Priya Aradhya; Rastogi, Neelkamal
Abstract: Ant‐lycaenid associations range from mutualism to parasitism and the caterpillars of some species of lycaenids are reported to enter ant nests for shelter, diapause, or pupation. The present study aimed to examine the nature of the association between Euchrysops cnejus (Fabricius) (Lepidoptera: Lycaenidae) and Camponotus compressus (Fabricius) (Hymenoptera: Formicidae) worker ants on the extrafloral nectary‐bearing cowpea plant, Vigna unguiculata (L.) Walp. (Fabaceae). The abundance patterns of the ants and the lycaenid caterpillars together with the spatial patrolling patterns of the ants on the plants revealed that ant abundance increased with the occurrence of the lycaenid caterpillars and the ants preferred the lycaenids over the extrafloral nectar. Camponotus compressus worker ants constructed a shelter at the cowpea plant base after interaction with one or more lycaenid caterpillar(s) and tended the caterpillars and pupae till the emergence of the butterfly. The ant‐constructed shelters (ACSs) inhabited by the minor caste workers (13 ± 1.3 ants per ACS), were utilized by the caterpillars to undergo pupation. The ants confined their activities predominantly to tending the pod‐feeding caterpillars and the solitary pupa within each ACS. It appears that the behavior of the tending worker ants is modulated by the lycaenid vulnerable stages. Abstract : This study concerns the association between Camponotus compressus (Hymenoptera: Formicidae) ants and the gram blue, Euchrysops cnejus (Lepidoptera: Lycaenidae), on extrafloral‐nectary bearing cowpea plants, Vigna unguiculata (Fabaceae). Based on long‐term field experiments and observations, we report that the ants construct a shelter for the pupae near the lycaenid‐harboring cowpea plants and tended the caterpillars and pupae till the emergence of the butterfly.